MODERN INDIAN MUSLIMS AND IQBAL - Javaid Iqbal (International Institute of Islamic Thought, 1997)
The book The Reconstruction of Religious Thought in Islam, also known as the Madras Lectures of Iqbal, has been translated into Urdu as Tashkeel-e Jadid Ilahiyat-e Islamia. In light of this work, I have chosen to address the topic: “Iqbal and the Concept of an Islamic State in Modem Times.” First, however, it is necessary to give some background to Iqbal’s lectures. This book has remained the least noticed work of Iqbal, although it deserves much more attention. The main reason for this neglect is that these lectures were addressed to and later published for Muslims of the new generation. Iqbal was aware that these Muslims could not remain aloof from the values of modem westem culture. It was therefore necessary for the Muslims to remain Muslim and, at the same time, to become modem. Since this book discussed modernity in Islam, the ulama were very annoyed with it. Its Urdu translation was delayed, because it was feared that the translation might provoke the ulama’s wrath and that they might consider it a presentation of a new religion, like Akbar‘s Dine Ilahi, or a distortion of religion under the pretext of reinterpretation. Many objections were raised. For instance, the late Sulaiman Nadvi wrote that it would have been better had this book not been published. Abul Hasan Ali Nadvi wrote: I do not consider Iqbal an innocent and pious person or a religious guide or an Imam Mujtahid, nor do I cross the limits, as his staunch supporters do, while acknowledging and praising his works. I consider that Hakeem Sinai, Attar and Arif Rumi were far ahead of him in respecting and following the Shariat, ...